2015
DOI: 10.1183/09031936.00002115
|View full text |Cite
|
Sign up to set email alerts
|

Increased alveolar soluble annexin V promotes lung inflammation and fibrosis

Abstract: The causes underlying the self-perpetuating nature of idiopathic pulmonary fibrosis (IPF), a progressive and usually lethal disease, remain unknown. We hypothesized that alveolar soluble Annexin V contributes to lung fibrosis, based on the observation that human IPF BALF containing high Annexin V levels promoted fibroblast involvement in alveolar epithelial wound healing that was reduced when Annexin V was depleted from the BALF. Conditioned medium (CM) from AEC2 treated with Annexin V, but not Annexin V per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…These are a family of tyrosine kinase receptors, which include Her1 (epidermal growth factor receptor (EGFR)), Her2, Her3 and Her4. Several of these receptors have reported roles in epithelial remodeling, epithelial proliferation and are found to play significant roles in models of fibrosis 44 45 46 . Further dysfunction within this pathway is supported by the finding of enrichment within the downregulated proteome for EGFR (Her1) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These are a family of tyrosine kinase receptors, which include Her1 (epidermal growth factor receptor (EGFR)), Her2, Her3 and Her4. Several of these receptors have reported roles in epithelial remodeling, epithelial proliferation and are found to play significant roles in models of fibrosis 44 45 46 . Further dysfunction within this pathway is supported by the finding of enrichment within the downregulated proteome for EGFR (Her1) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin 5 is an anticoagulant protein that acts as an indirect inhibitor of thromboplastin-specific complex and PLA2 [ 72 79 ]. Previous studies suggested an important roles for annexin 5 in the inflammation of tissues such as the heart, vascular endothelial cells, and lung, and in systemic sepsis [ 80 81 82 83 84 ]. Modifications in annexin 5 expression have been implicated in cardiovascular diseases [ 85 ], cancers [ 72 ], osteoarthritis [ 86 ], and rheumatoid arthritis [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were tyrosine kinase receptor families, including Her1 (epidermal growth factor receptor (EGFR)), Her2, Her3, and Her4. Several of these receptors have been reported to play an important role in epithelial remodeling and epithelial hyperplasia, and have been found to play an important role in the brosis model [41][42][43]. EGFR (c-erbB1) played a key role in the maintenance and repair of epithelial tissue.…”
Section: Discussionmentioning
confidence: 99%